Estimation of Sediment Distribution Based on Bathymetry Alteration (2014-2016) in the Inner Bay of Ambon, Maluku, Indonesia - Guntur Adhi Rahmawan; Wisnu Arya Gemilang; Ulung Jantama Wisha; Ruzana Dhiauddin; Koko Ondara (Jurnal Segara, 2019)
The development of Ambon city is centered around Ambon Bay. As the major area of marine and social activities, changes occurred directly affect to seawater degradation. Sedimentation is the main issue that has been occurring. Marine ecosystem can be potentially hampered by the high rate of sedimentation in the Inner Bay of Ambon (TAD). This study aimed to determine the distribution of sediment volume within the bay. Bathymetry of TAD was surveyed using transducer (Echosounder Echo track CVM Teledyne Odom Hydrographic Single Beam), which the depth of certain position was connected to GPS to record all the position data accurately. The field data are then analyzed spatially modelled in the form of 2D and 3D maps, overlaid with the past bathymetry data to calculate the bathymetry alteration and sediment volume estimation during 2014-2016. The depth of TAD in 2014 ranged between 0 - -42 meters, while, in 2016 the water depth slightly changed to 0 – -44 meters. The reduction of the water depth is observed in the 25 – 125 m from shoreline, where the bed thickness changes observed ranging from 0.1 - 1.4 m. Total volume of sediment augmentation reaches 13,236,182 m3 that covers about 67.67 Ha. Tidal current, that ranged averagely from 0-1.2 m/s, has a tremendous influence on sediment transport in TAD. The bay mouth, that is a semi-enclosed enclosed area, triggers sediment accumulation due to the weak tidal current transport. If ongoing, these conditions may endanger the environment and biota survival ability.